Mathematical Modeling of Measles Disease Spread with Treatment Factors and Batik Motifs from the Simulation - Maghfiroh, Neli; Febiani, Dhela; Sugiyanto, Sugiyanto (Proceeding International Conference on Religion, Science and Education, 2026)
This study analyzes the application of batik motif concepts in mathematical modeling of measles disease spread using the SMEIUR (Susceptible–Exposed–Medicated–Infected–Untreated–Recovered) model, which takes into account treatment aspects. The SMEIUR model was chosen to describe the dynamics of disease spread more comprehensively and in detail by distinguishing between individuals who receive treatment and those who do not, thus providing a more accurate epidemiological picture in the community. The batik motif approach was applied as a medium for mathematical visualization, where batik patterns symbolize order, symmetry, and relationships between compartments in a dynamic population system. Each motif represents the interaction between groups of individuals who are susceptible, exposed, receiving treatment, and recovering from infection. The results of the study show that an increase in the level of treatment can significantly reduce the number of infected individuals and accelerate the achievement of endemic equilibrium. The integration of traditional batik motifs with epidemiological mathematical models is expected to be an interesting innovation in combining cultural values and science, helping the community not only to understand the dynamics of infectious disease spread, such as measles, scientifically, but also to enrich visual communication approaches that are closer to local culture. This interdisciplinary approach opens up opportunities for a more comprehensive understanding of epidemiology through art, while providing new alternatives in public health education that are culturally sensitive and easily accepted. This study proves that the combination of mathematics, art, and culture can be an effective strategy in promoting awareness and control of infectious diseases.